frnpact ai nyrnph ta adultiood-switch and o! adult !ood-stress an Nezara viridula (Honiiptera: Penlatomidae) bialogy - Panizzi, Antônio A.; Meneguim, Ana M.; Rossini, Maria C. (Pesquisa Agropecuaria Brasileira, 2013)
Laboratory studies of aduil southem green stink bug Nezara viridula (1..) demonsvatod that this species exhibited diflerences i n perlomiance (i.e.,survivorship, Iongevity, reproductive paianieters, and body weight changee) depending on the different food-switches from nymph to adult and on the nutiltional stress imposed tu adulta, In general, survivorship and longevity of adulta on immalure soybean [G)ycine max (L) Merrili] pod - ISP - and on mature soybean seed - MSS - were greater when nymphs fed ISP, cornpared to adulta that were fed green bean (Phaseo/us vulgar/a L) pod - GBP - when nymphs. Nyrnphs reared on iSP, led soybean atem + leal (SSL) or starved when adulta, showed reduced longevity. Reproduclive performance of temales o? N. viridula fed GBP, eilher as nymphs ar as adulta, was smaliercompared lo females fed ISP or MSS; no temales reproduced when ted SSL ar slarved. In most toada females fed ISP as nyrnphs showed greater and earlier penks of weight gain than those Ind GBP as nymphs. Daily weightgaln o? N. vir/da/a, previousiy starved for 24 hours, was greater during the Ist than dudng the 2nd week of adult um. Total body Iipid wntent decreased due to continuous Starvation.